Make-or-Buy Analysis : Case Automotive Company - Neuvonen, Eevi (My University, 2022)
Abstract Outsourcing is an ever more popular strategy that companies utilize to achieve high-level performance in the competitive business environment they operate in. The definition of make-or-buy decision divides between the options to acquire products or services from a supplier, produce them in-house or collaborate to form a partnership. Any of these options can take place either domestically or abroad. Make-or-buy analysis focuses on the process that is taken to evaluate outsourcing possibilities against in-house production with the goal of finding the optimal solution. This study aims at developing a tool to support make-or-buy analysis in the automotive industry, at the same time linking the decision and the drivers affecting its successfulness to the wider context of resource-based view (RBV) and transaction cost economics (TCE). A review of existing research on the topic is conducted to form a framework on which to base the empirical part of the study. A single case study is chosen as a research method to explore the topic further in practice. Qualitative analysis criteria are categorized in four groups: competitive advantage and capabilities, coordination and interaction, flexibility and risks, whereas personnel, running, logistics, facility and overhead costs are identified as main cost categories. A spreadsheet-based tool is created to calculate the optimal unit cost and to compare it with the current arrangement. The optimization tool is complemented with a sensitivity analysis and Monte Carlo simulation that shed light on how the outcome would be impacted in case the inputs would change. Based on expert interviews and discussions, analysis criteria are validated and adjusted in the context of automotive industry. The tool is tested in an empirical real-life case example. Results reveal a clear overview of the advantages and disadvantages of each option from the perspective of each criterion. Competitive advantage and coordination and interaction analysis support continuing to outsource while risk and cost analysis point towards manufacturing in-house. Results from flexibility analysis are twofold. The case study and feedback from case company imply the use of the tool can help support make-or-buy analysis and make more informed outsourcing decisions

Tiivistelmä Ulkoistamisesta on tullut yrityksissä yhä yleisempää, ja se nähdään yhtenä keinona vastata kilpailuympäristön vaatimuksiin. Make-or-buy-päätöksen voidaan määritellä liittyvän tuotteiden tai palveluiden hankkimiseen toimittajalta, niiden tuottamiseen yrityksen sisällä tai kumppanuuden muodostamiseen toimittajan kanssa. Jokainen näistä vaihtoehdoista voidaan toteuttaa sekä jossakin lähellä että kauempana. Make-or-buy-analyysi keskittyy prosessiin, jossa verrataan ulkoistamismahdollisuuksia omaan tuotantoon, tavoitteena löytää optimaalinen ratkaisu. Tämän tutkimuksen tarkoituksena on kehittää työkalu autoteollisuuden make-or-buy-analyysin tueksi. Samalla sidotaan make-or-buy-päätös ja sen onnistumiseen vaikuttavat tekijät laajempaan kontekstiin resurssipohjaisen näkökulman (engl. resource-based view) ja transaktiokustannusteorian (engl. transaction cost economics) kautta. Lisäksi toteutetaan katsaus aiheeseen liittyvään aiempaan tutkimukseen, jotta voidaan muodostaa viitekehys empiirisen osion tueksi. Tutkimusmenetelmäksi on valittu yksittäistapaustutkimus, jotta aihetta voidaan ymmärtää syvällisesti käytännössä. Laadulliset analyysikriteerit jaetaan neljään ryhmään: kilpailuetu ja kyvykkyydet, koordinaatio ja vuorovaikutus, joustavuus ja riskit. Tärkeimmät kustannusryhmät ovat tila-, henkilöstö-, logistiikka- ja yleiskustannukset sekä juoksevat kustannukset. Optimaalisen yksikkökustannuksen laskemiseksi ja sen vertailemiseksi nykyiseen yksikkökustannukseen kehitettiin taulukkolaskentatyökalu. Työkalua täydennettiin herkkyysanalyysillä ja Monte Carlo -simulaatiolla, jotka auttoivat ymmärtämään miten syöttöarvojen muutos vaikuttaa lopputulokseen. Analyysikriteerit validoitiin ja mukautettiin autoteollisuuteen soveltuviksi asiantuntijahaastattelujen ja -keskustelujen pohjalta. Työkalua testattiin konkreettisella esimerkkitapauksella. Tulosten perusteella saatiin selkeä kuva vaihtoehtojen hyödyistä ja haitoista eri kriteerien näkökulmista. Kilpailuedun ja kyvykkyyksien sekä koordinaation ja vuorovaikutuksen näkökulma tuki nykyisen ulkoistamisratkaisun jatkamista, kun taas riskien ja kustannusten kannalta oma tuotanto vaikutti paremmalta vaihtoehdolta. Joustavuuden osalta tulokset tukivat osin ulkoistamista ja osin omaa tuotantoa. Tapaustutkimuksen ja toimeksiantajayrityksen palautteen perusteella voidaan sanoa, että työkalu voi olla hyödyksi make-or-buy-analyysissä ja tukea tietoon perustuvien ulkoistamispäätösten tekemistä.
Keywords: Make-or-buy analysis, outsourcing, automotive industry